Association of passive exposure of pregnant women to environmental tobacco smoke with asthma symptoms in children - Xepapadaki, P.; Manios, Y.; Liarigkovinos, T.; Grammatikaki, E.; Douladiris, N.; Kortsalioudaki, C.; Papadopoulos, N. G. (Pediatr Allergy Immunol, 2009)
Environmental tobacco smoke (ETS) is a significant risk factor for the presence and increased severity of asthma- and allergy-related symptoms in children. Smoking during pregnancy has detrimental effects on asthma-associated outcomes in childhood. Whether passive exposure of pregnant women to ETS may also lead to asthma in their offspring, is not known. The aim of this study was to investigate the association of passive exposure of pregnant women to ETS and asthma- and/or allergy-related symptoms in Preschool children. Cross-sectional data were collected with questionnaires from 2374 Preschool children, recruited from public and private nurseries and day-care centers. Parental smoking was significantly associated with wheezing symptoms in their children. Mother's active smoking during pregnancy significantly increased the risk for occurrence of asthma symptoms and/or medically diagnosed asthma in Preschool children in a dose-dependent manner. Passive exposure to ETS, mainly during the third trimester of pregnancy, was significantly associated with asthma- and allergy-related symptoms after adjusting for several confounders in a multivariate analysis (current wheeze: OR = 1.42, 95% CI = 1.06-1.91, pruritic rash ever: OR= 1.45, 95% CI = 1.01-2.08). Passive exposure of pregnant women to ETS during the third trimester is positively associated with asthma- and allergy-related symptoms in their Preschool age children. Public health policies should be oriented not only towards smoking cessation, but also reinforce elimination of ETS exposure of pregnant women.
Keywords: Asthma Child Child; Preschool Environmental Exposure Female Humans Infant Male Pregnancy Pregnancy Trimester; Third Prenatal Exposure Delayed Effects Questionnaires Respiratory Sounds Risk Factors Smoking Tobacco Smoke Pollution